Parkinson's Disease Dementia - Robottom, Bradley J.; Weiner, William J. (Current Psychiatry Reviews, 2009)
Parkinson's disease (PD) is the second most common neurodegenerative illness diagnosed in the United States. Dementia is recognized to be common in PD, occurring in 19-78&percnt of patients depending upon the definition used. The cognitive syndrome of Parkinson's disease dementia is predominantly one of executive dysfunction, and it has a profile that is distinct from Alzheimer's dementia. Neuropsychiatric problems frequently accompany Parkinson's disease dementia and lead to considerable therapeutic challenges. This review focuses on the epidemiology, clinical characteristics, pathology, neuroimaging, diagnosis, and treatment of Parkinson's disease dementia.
Keywords: Parkinson' s disease